INCREASING STUDENTS’ ABILITY IN READING COMPREHENSION THROUGH PQRST STRATEGY (LESSON STUDY BASED FOR THE FIRST YEAR AT SMA N 1 PEUSANGAN): INCREASING STUDENTS’ ABILITY IN READING COMPREHENSION THROUGH PQRST STRATEGY (LESSON STUDY BASED FOR THE FIRST YEAR AT SMA N 1 PEUSANGAN) - Harmita Zaini; Silvi Listia Dewi (Department of English Education, Faculty of Teacher Training and Education, Almuslim University, 2022)
The title of this research is increasing students’ ability in reading comprehension through pqrst strategy in lesson study. The objective of this research is: To describe the students’ achievement in reading comprehension by using PQRST strategy at SMAN Peusangan and to know the students’ respond through prediction strategy to the reading comprehension in recount text of grade ten students of SMA N 1 Peusangan. The data collected through the observation sheet, text, and test. This research uses lesson study in the teaching process and this research was done in two meeting. The research subject was the first year students of SMA N 1 Peusangan. The sample of this resarch was were 21 students. The data was collected through the observation sheet, text, and test.The data was analyzed through Quantitative Recount Text in conducting the research. The procedure of lesston study of lesson study: Plan, Do, See. After the researcher was done all the the steps of action the result of students’ means score for the first meeting was 66,90 it does not meets the criteria, then the researcher decide to continue for the second meeting the students’ score was 85 and it meets the criteria of SMA N 1 Peusangan. The finding of the researcher also showed that PQRST Strategy in Lesson Study model can icreas the students’ reading comprehension, it was showed from the result of students mastery recoun text. The result of this study indicate that reading can add insight and new vocabulary, because by reading students would get a lot of new words that were not yet know, therefore reading be able to increase students’ vocabulary and the steps of the PQRST strategy can help students understand the text more easly bisides that students also mindset broad and sharp.